p-hydroxy benzaldehyde attenuates intestinal epithelial barrier dysfunction caused by colitis via activating the HNF-1β/SLC26A3 pathway - Liu, Meng; Wang, Yuhui; Xu, Xiaotian; Guan, Guoqiang; Zhang, Shu; Zhu, Shengnan; Liu, Yang; Zhu, Yizhun; Duan, Xiaoqun (Frontiers in Pharmacology, 2024)
Intestinal epithelial barrier dysfunction is intricately linked to the pathogenesis of ulcerative colitis (UC). Dietary interventions that bolster intestinal epithelial barrier function can effectively thwart UC onset. Our prior research revealed that p-Hydroxy benzaldehyde (HD), a phenolic compound from Nostoc commune (an edible cyanobacterium), markedly upregulated the expression of E-cadherin, a pivotal protein in intestinal mucosa, thereby mitigating mucosal damage in mice afflicted with dextran sulfate sodium (DSS)-induced colitis. Nevertheless, the precise molecular mechanisms underpinning HD's ameliorative effects on intestinal epithelial barrier dysfunction remain elusive. This study elucidates HD's role in forestalling intestinal epithelial barrier disruption under colitis conditions. Mechanistic investigations revealed that HD fortifies TJs and AJs expression via the HNF-1β/SLC26A3 pathway, thus preserving the lower intestinal epithelial barrier's integrity in UC. In recent years, several natural products have been recognized for their unique multi-target actions, good tolerability and low-cost attracting much attention (Zhou, Wang, & Yan, 2023) . Natural products are abundant in nature and generate numerous structurally diverse secondary metabolites, including a large number of small molecule compounds with anti-inflammatory activity (Zhou et al., 2023). Nostoc commune, a cyanobacterium vegetable with significant nutritional benefits, is recognized for its anticancer, anti-inflammatory, and antimicrobial attributes (Z. Li & Guo, 2018) . Our previous research has shown that p-hydroxy benzaldehyde (HD), a phenolic compound from Nostoc commune, can relieve colitis, reduce inflammation, and increase E-cadherin expression (Xu, Wei, Yang, Liu, & Duan, 2021) . Yet, the exact molecular mechanisms through which HD ameliorates intestinal epithelial barrier dysfunction remain to be elucidated. Studies have shown that E-cadherin is closely related to mucosal barrier function, mucin 2 (MUC2) and goblet cell number. E-cadherin loss interferes with goblet cell maturation and migration (Schneider, Dahlhoff, Horst, Hirschi, & Kolligs, 2010) , reducing the number of goblet cells, thereby reducing the secretion of mucin MUC2 and damaging mucosal barrier function (Y. Liu et al., 2023) . Based on these findings, this study aims to elucidate HD's protective effects on the intestinal epithelial barrier and its mechanisms by developing in vitro and in vivo models of intestinal barrier injury, thereby assessing its therapeutic potential for UC.